2011
DOI: 10.1111/j.1447-0756.2010.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey report of gamete donors' and recipients' preferences regarding disclosure of third party reproduction outcomes and genetic risk information

Abstract: All programs participating in gamete donation should establish a comprehensive disclosure policy, including consents that are built upon effective lines of communication between clinical staff and legal counsel assuring that parentage, relinquishment, and re-contact information in donor-recipient agreements are consistent with clinic consent documents and desires of both parties; All decisions must be adequately documented and honored and long-term counseling needs should be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…They admitted that updated medical and genetic history was valuable, especially in cases of medical emergencies. These results are consistent with a questionnaire-based study done in an oocyte donor programme (Lindheim et al, 2011). The sample of 382 participants comprised predonation donors, donors undergoing the process and ante-or post-partum recipients.…”
Section: The Minimal Justification Of a Gedrsupporting
confidence: 87%
See 2 more Smart Citations
“…They admitted that updated medical and genetic history was valuable, especially in cases of medical emergencies. These results are consistent with a questionnaire-based study done in an oocyte donor programme (Lindheim et al, 2011). The sample of 382 participants comprised predonation donors, donors undergoing the process and ante-or post-partum recipients.…”
Section: The Minimal Justification Of a Gedrsupporting
confidence: 87%
“…At first, to respect a plurality of values, a GEDR would have to deal with variable opinions regarding the right to be informed of unanticipated testing results, adverse outcomes (Lindheim et al, 2011) and predispositions to heritable adult-onset disorders (Daar and Brzyski, 2009). Similarly, a GEDR may confront affected parties with the possibility of a medical intervention to reduce genetic risk, it may entail different notions of genetic risk (Lindheim et al, 2011) and different conceptions of the severity of disease (Wertz and Knoppers, 2002;C Bouffard and F Duplain-Laferrière, unpublished data). Lindheim et al (2011) also suggested that some people would fear that participating in a GEDR would create a legally binding obligation to transmit truthful medical information.…”
Section: The Recognition Of Beneficiaries' Continued Free Agencymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of attitudinal changes towards openness in relation to donor conception includes the increasing likelihood that parents will disclose the use of a gamete donor to their children (Blake et al , 2010; Söderström-Anttila et al , 2010), that parents of donor-conceived children want to make contact with ‘donor siblings’ (Freeman et al , 2009), that some anonymous donors welcome the removal of donor anonymity (Daniels et al , 2012), that change in donor anonymity legislation has not necessarily resulted in a decline in the number of men willing to donate sperm (Shukla et al , 2013), and the influence of counselling on donors' and recipients' willingness to disclose the use of donor gametes to children conceived as a result (Hammarberg et al , 2008). Donor-conceived people's right to medical and genetic information about the donor is asserted (Lindheim et al , 2011; Ravitsky, 2012). Contemporary evidence suggests that it is best for donor-conceived children to be informed by their parents at an early age about the means of their conception (Nuffield Council on Bioethics, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A study of previous oocyte donors [12] explored the medical and psychosocial issues which have emerged from having been a donor, while another study [13] reported on the views of oocyte donors (pre-donation, and current) regarding similar issues that were explored with the sperm donors in the current study.…”
Section: Introductionmentioning
confidence: 99%